Safety of oral nemonoxacin: A systematic review of clinical trials and postmarketing surveillance - Yuan, Jinyi; Zhang, Xiaoping; Chen, Jing; Zhang, Yueyuan; Zhu, Fengjia; Huang, Haihui (Frontiers in Pharmacology, 2022)
Background: Postmarketing safety analysis is an effective supplement for new drugs in clinical practice. Therefore, we aimed to systematically assess the safety of oral nemonoxacin malate, the first approved C-8-methoxy nonfluorinated quinolone, in clinical studies and via postmarketing safety surveillance. Methods: We electronically and manually searched and screened safety data (including premarketing and postmarketing data) of oral nemonoxacin from clinical registries. We standardized and summarized the reported adverse events (AEs) according to the Medical Dictionary for Regulatory Activities System Organ Class and Preferred Terms. We summarized and reported the number and frequency (%) of the AEs and serious AEs in patients with community-acquired pneumonia (CAP) and in specific patients. Results: Three Phase II/III comparator studies (n = 670, nemonoxacin), one Phase IV study (n = 461), two special population pharmacokinetic studies (n = 40), four observational studies (n = 1,852), and one 5-year postmarketing surveillance project (n = 257,420) were included in this study. The Phase II/III studies showed that the commonly reported drug-related AEs were similar for oral 500 mg nemonoxacin and levofloxacin treatments, which mainly included increased alanine aminotransferase levels (4.4% vs. 2.5%), neutropenia (2.5% vs. 4.4%), nausea (2.5% vs. 1.6%), and leukopenia (2.3% vs. 3.2%). No drug-related deaths were reported. Postmarketing safety surveillance revealed that known adverse drug reaction characteristics were generally unchanged. Pharmacokinetic data suggested that dose adjustment was not necessary in elderly patients, which was confirmed by a Phase IV study in an elderly population, in patients with renal impairment with CLcr ≥ 50 mL/min, and in those with mild-to-moderate hepatic impairment. Conclusion: Clinical trial data of approximately 1450 patients and postmarketing data of >257,420 patients suggest that nemonoxacin is generally well tolerated and can be a suitable alternative to fluoroquinolones for patients with CAP.